TELEREGULATION IN GASTROENTEROLOGY AND THE BOTTLENECK OF SPECIALIZED HEALTH CARE - Leticia ROSEVICS; Adriana Zanoni DOTTI; Elisandre Caroline dos Santos CERUTTI; Fernanda Guimarães BIANCHI; Kátia Cristina KAMPA; Mônica Rosas ROCHA (Arquivos de Gastroenterologia)
ABSTRACT Background: Increasing population size and the presence of bottlenecks in access to specialized health care demonstrate the importance of developing measures for better clinical management. The implementation of teleregulation is expected to bring greater resolution in the system. Objective: The objective of the present study was to evaluate the results of teleregulation in gastroenterology for the resolution of referrals in a large Brazilian city. Methods: We carried out a retrospective cross-sectional study of primary health care teleregulation requests for gastroenterology in a Brazilian city. Data were collected from October 2022 to June 2023 in patients aged >18 years. Patient demographic data, the reason for requesting screening, and screening outcomes were collected. Requests for reassessment were excluded. Results: Of the 3,000 teleregulation sessions screened in the study period, 71.1% were included, of which 68.17% were for women with a mean age of 54.32±16.19 years. Among the reasons for referral, 1,368 (64.13%) were to request examinations, 568 (26.63%) to discuss conduct and 197 (9.24%) to request a referral to a specialist. Ten percent of cases required referral to a specialist, 6.61% were incorrect requests and 14.95% were prioritized. Conclusion: The present study highlights that teleregulation represents an important tool in health management, being able to bring resolution in 89.9% of cases.